Illuminating gravitational waves: A concordant picture of photons from a neutron star merger - Kasliwal, MM; Nakar, E; Singer, LP; Kaplan, DL; Cook, DO; Van Sistine, A; Lau, RM; Fremling, C; Gottlieb, O; Jencson, JE; Adams, SM; Feindt, U; et al. (American Association for the Advancement of Science, 2017)
Merging neutron stars offer an excellent laboratory for simultaneously studying strong-field gravity and matter in extreme environments. We establish the physical association of an electromagnetic counterpart (EM170817) with gravitational waves (GW170817) detected from merging neutron stars. By synthesizing a panchromatic data set, we demonstrate that merging neutron stars are a long-sought production site forging heavy elements by r-process nucleosynthesis. The weak gamma rays seen in EM170817 are dissimilar to classical short gamma-ray bursts with ultrarelativistic jets. Instead, we suggest that breakout of a wide-angle, mildly relativistic cocoon engulfing the jet explains the low-luminosity gamma rays, the high-luminosity ultraviolet-optical-infrared, and the delayed radio and x-ray emission. We posit that all neutron star mergers may lead to a wide-angle cocoon breakout, sometimes accompanied by a successful jet and sometimes by a choked jet.